MICKIEWICZ I TREMBECKI – JESZCZE RAZ (JUŻ SIĘ Z POGODNYCH NIEBIOS…) - Chachulski, Tomasz (Colloquia Litteraria, 2017)
This short sketch focuses on the excerpt from Adam Mickiewicz’s early poem „Już się z pogodnych niebios…” (1818), where the young poet specifies the rules of receiving new members into the Philomath Society (Towarzystwo Filomatów). Mickiewicz drew the basic motif of that part of the poem from the last section of Stanisław Trembecki’s Classicist descriptive poem Sofijówka (verses 425nn). What in an Enlightenment poem characterised by clearly libertine and pro-Russian tendencies served the representative of the Stanislavian times to build an individual microethics programme which was concerend exclusively with one’s closest circle and their attitude towards themselves, in a programmatic poem by a young Romantic became a set of rules to select righteous and trustworthy poeple who would not take fright in front of adversities and would resist a variety of pressures. Trembecki’s poem, however, also contained yearning for a forseeable future and nostalgia for what had been lost.